2010
DOI: 10.1308/003588410x12518836439047
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Improving Outcomes Guidance on the management and outcomes of patients with carcinoma of the penis

Abstract: INTRODUCTION The Improving Outcomes Guidance (IOG) for patients with carcinoma of the penis states that treatment should be provided supraregionally to populations of 4 million or greater who treat over 25 cases of penis cancer each year. This study assesses the impact of this guidance on the management and outcomes of patients with the disease in our region. PATIENTS AND METHODS We retrospectively compared the records of 44 patients with carcinoma of the penis treated in our institution between 1969 and 1990 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 2 publications
2
22
0
2
Order By: Relevance
“…Philippou et al [28] demonstrated that the rates of local recurrence and 5-year CSS after penile-sparing surgery were 8.9% and 91.7%, respectively, during a mean follow-up of 26 months. Bayles and Sethia [29] supported these excellent oncologic outcomes, reporting rates of local recurrence and cancer-specific mortality of 4.8% and 10.7%, respectively. In this study, the operation method (partial vs. total) was not significant for CSS.…”
Section: Discussionmentioning
confidence: 82%
“…Philippou et al [28] demonstrated that the rates of local recurrence and 5-year CSS after penile-sparing surgery were 8.9% and 91.7%, respectively, during a mean follow-up of 26 months. Bayles and Sethia [29] supported these excellent oncologic outcomes, reporting rates of local recurrence and cancer-specific mortality of 4.8% and 10.7%, respectively. In this study, the operation method (partial vs. total) was not significant for CSS.…”
Section: Discussionmentioning
confidence: 82%
“…Another recent study by Bayles et al compared outcomes of patients with PCa before and after their service was centralised in Norwich. 8 Their results demonstrated a significant increase in the amount of penis-preserving surgery and nodal surgery with an associated decrease in mortality since the development of their supra-regional centre. 8 In our study there were no significant differences in cancer specific survival (CSS) or recurrence free survival (RFS) between both groups.…”
Section: Discussionmentioning
confidence: 97%
“…8 Their results demonstrated a significant increase in the amount of penis-preserving surgery and nodal surgery with an associated decrease in mortality since the development of their supra-regional centre. 8 In our study there were no significant differences in cancer specific survival (CSS) or recurrence free survival (RFS) between both groups. However, our KaplineMeier curves demonstrate a trend for poorer survival rates and higher recurrence rates in patients that were initially managed in a SRC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Met deze doelstelling zouden acht tot tien centra moeten volstaan [22]. Een recente analyse naar de effectiviteit hiervan leidt tot resultaten die we in Nederland ook hebben gezien: meer weefselsparende behandelingen en betere overleving [23].…”
Section: Andere Effecten Van Concentratieunclassified